APPLICATION OF E-CRM IN MUSHROOM SALES (A CASE STUDY OF BOMBOM BUSINESS) - Citra Novianti; Yessica Siagian; Ahmad Muhazir (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Bombom business is a business engaged in the sale and cultivation of mushrooms, where there are several types of mushrooms that are cultivated such as oyster mushrooms, ear mushrooms, straw mushrooms, button mushrooms, and toadstools. The location of this business is in Mangkai Baru Village, Lima Puluh District, Batu Bara Regency. Currently the process of selling mushrooms is only done manually, namely by coming directly to the business location and in marketing this business is still doing marketing directly through banners in front of the house and this business does not yet have a sales system that covers a wide area to market its products to a wider area. as outside the province. The method used in this research is to apply Electronic Customer Relationship Management (E-CRM). The results of implementing E-CRM (Electronic Customer Relationship Management) mushroom sales in the bombom business can improve service to customers and can increase mushroom sales in the bombom business. Based on the results of these studies, it can be concluded that E-CRM can help in the sale of mushrooms which can increase sales and can retain customers.